The influence of aspect ratios and wall heating conditions on flow and passive pollutant exposure in 2D typical street canyons. (15th January 2020) - Hang, Jian; Chen, Xieyuan; Chen, Guanwen; Chen, Taihan; Lin, Yuanyuan; Luo, Zhiwen; Zhang, Xuelin; Wang, Qun
Abstract: Deep street canyons and unfavourable meteorological conditions usually induce high pollutant exposure. Validated by experimental data, this paper employs computational fluid dynamic simulations with RNG k-ε model to investigate the flow, and passive pollutant dispersion within scale-model two-dimensional street canyons( H  = 3 m). As a novelty, this paper quantifies the impacts of various wall heating scenarios(bottom, leeward/windward wall and all-wall heating), ambient velocity( U ref  = 0.5–2 m s −1, Froude numbers Fr =  0.25–4.08, Reynolds numbers Re  = 95602–382409) and aspect ratios(building height/street width, AR  = 0.5, 0.67, 1, 2, 3) on personal intake fraction for entire streets(< P_IF> ). The governing equations are implicitly discretized by a finite volume method (FVM) and the second-order upwind scheme with Boussinesq model for quantifying buoyancy effects. The SIMPLE scheme is adopted for the pressure and velocity coupling. In most isothermal cases, one-main-vortex structure exists as AR  = 0.5–3(< P_IF>  = 0.43–3.96 ppm and 1.66–27.51 ppm with U ref  = 2 and 0.5 m s −1 ). For non-isothermal cases with Fr  = 4.08( U ref  = 2 m s −1 ), wind-driven force dominates urban airflow as AR  = 0.5–1 and four heating conditions attain similar < P_IF> (0.39–0.43 ppm, 0.57–0.60 ppm, 0.91–0.98 ppm). As AR  = 2, windward and all-wall heating get two-vortex structures with greater < P_IF> (3.18–3.33 ppm) than others(< P_IF> =  2.13–2.21 ppm). As AR  = 3, leeward-wall heating slightly reduces < P_IF> (~3.72–3.96 ppm), but the other three produce two-vortex structures with greater < P_IF> (6.13–10.32 ppm). As Fr  = 0.25( U ref  = 0.5 m s −1 ), leeward-wall heating always attains smaller < P_IF> (1.20–7.10 ppm) than isothermal cases(1.66–27.51 ppm) as AR  = 0.5–3, however the influence of the other three is complicated which sometimes raises or reduces < P_IF> . Overall, smaller background wind speed ( Fr  = 0.25) with two-vortex structures attains much larger < P_IF> . Special attention is required at night(all-wall heating), noon(bottom-heating) and cloudy period(no-wall heating) as AR  = 2–3, while it is during windward-wall heating and cloudy period for AR  = 0.5–1. Highlights: As Fr  = 4.08, wind-driven force dominates the urban airflow as AR  = 0.5–1. As Fr  = 0.25, most heating conditions would lead to a lower < P_IF> . Formation of single main vortex is the most efficient way to decrease the < P_IF>. Leeward heating condition always decreases the < P_IF > as Fr  = 0.25 and 4.08.